The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.2174/1573411011107030243
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Methods for Metallothionein Detection

Abstract: Metallothioneins (MTs) are a group of low molecular mass, cysteine-rich proteins with a variety of functions including involvement in metal homeostasis, free radical scavenging, protection against heavy metal damage, and metabolic regulation via Zn donation. The overexpression of MTs in proliferating cells is turning the attention to the study of MTs as novel promising marker of tumor diseases. Besides, levels of MTs in invertebrates and aquatic vertebrates well correlate with heavy metal pollution of an envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 97 publications
(60 citation statements)
references
References 254 publications
(266 reference statements)
4
54
0
2
Order By: Relevance
“…For these purposes, numerous analytical and biochemical methods are used [32,33], whereas the electrochemical ones seem to be the most sensitive [33][34][35]. Nevertheless, the tissue distribution can be well detected by immunohistochemistry, which was based for performing meta-analysis of metallothionein as an immunohistochemical marker of cancer [36].…”
Section: Metallothionein Expressionmentioning
confidence: 99%
“…For these purposes, numerous analytical and biochemical methods are used [32,33], whereas the electrochemical ones seem to be the most sensitive [33][34][35]. Nevertheless, the tissue distribution can be well detected by immunohistochemistry, which was based for performing meta-analysis of metallothionein as an immunohistochemical marker of cancer [36].…”
Section: Metallothionein Expressionmentioning
confidence: 99%
“…Moreover, MREs is able to interact with many proteins, which can regulate MT expression (Miles et al, 2000). The chemicals producing free radicals as well as various organic solvents, such as ethanol (Waalkes et al, 1984), chloroform and alkylation agents can also induce the expression of MT (Ryvolova et al, 2011). It has been reported that the highest levels of MT expression is shown in the late G1 phase and during entering the S phase.…”
Section: Gene Regulation Of Mtmentioning
confidence: 99%
“…Furthermore, due to the increased metal binding capacity, MT has been suggested as a biomarker of both environmental and biological monitoring reflecting exposure to metal (Ryvolova et al, 2011). Since MT is present in most tissues and cell types, it is generally considered as a "house keeping" protein.…”
Section: Classification Of Mtmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been recently demonstrated that metallothioneins play an important role in the development and progression of some tumour diseases (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). Enhanced levels of MT in tumour cells are probably closely connected with cell proliferation (43,44).…”
Section: Introductionmentioning
confidence: 99%